2009
DOI: 10.1159/000207523
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive DNA probe linked to sex chromosomes in hybrids between Neotropical fish <i>Leporinus macrocephalus</i> and <i>Leporinus elongatus </i>(Characiformes, Anostomidae)

Abstract: Interspecific hybrids of fish can offer important advances in the zootechnical exploration of this animal group. However, hybrids can pose serious biological risks to the environment and natural populations, making genetic characterization and monitoring of hybrids produced in fish culture important concerns. In the present study, individuals of the hybrid ‘Piaupara’ were characterized by fluorescence in situ hybridization (FISH) using sex-specific probes to differentiate the respective parental contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…When this repetitive DNA was used as a probe in L. elongatus metaphase chromosomes, homology between this sequence and the heterochromatic regions associated to the NOR was seen, beyond the regions in the sexual chromosomes described previously by Parise-Maltempi et al (2007). From this similarity, studies utilizing molecular techniques should be implemented to potentially identify the relationship and structural organization of these sequences associated with the nucleolar regions in L. elongatus, since these sequences were not observed in L. macrocephalus (Hashimoto et al 2009). …”
Section: Discussionmentioning
confidence: 82%
“…When this repetitive DNA was used as a probe in L. elongatus metaphase chromosomes, homology between this sequence and the heterochromatic regions associated to the NOR was seen, beyond the regions in the sexual chromosomes described previously by Parise-Maltempi et al (2007). From this similarity, studies utilizing molecular techniques should be implemented to potentially identify the relationship and structural organization of these sequences associated with the nucleolar regions in L. elongatus, since these sequences were not observed in L. macrocephalus (Hashimoto et al 2009). …”
Section: Discussionmentioning
confidence: 82%
“…Interspecific fish hybrids are important models for cytogenetic studies because they inherit 1 chromosome set of each parental species, which allows the identification of differences and/or similarities between the chromosomes of the parental species [Porto-Foresti et al, 2008;Hashimoto et al, 2009a] including sex chromosomes [Hashimoto et al, 2009b]. The fish hybrid between the species Pseudoplatystoma corruscans and P. reticulatum , known under the vernacular name 'ponto e vírgula', has great economic importance in the Brazilian aquaculture [Campos, 2010].…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31][32] In the present study, retrotransposable elements in the Rex family were also abundant in other heterochromatic regions in Leporinus chromosomes, such as terminal positions and some interstitial segments. This distribution reflects the pattern expected for transposable elements distribution described by Kidwell,7 related to a low rate of recombination.…”
Section: Discussionmentioning
confidence: 76%
“…25 Recent studies of Leporinus have isolated, characterized, and correlated repetitive elements in these species to study the evolution of sex chromosomes, as well as to discriminate hybrid species. [26][27][28][29][30][31][32] Other studies have shown that repetitive sequences such as 5S rDNA may have different distributions among Leporinus species with or without heteromorphic sex chromosomes. 33 The high heterochromatic content in the chromosomes of Leporinus species, especially the sex chromosomes, demonstrates the presence of high numbers of repetitive sequences in the genomes of these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation